Studi Timbulan Dan Komposisi Sampah Rumah Tangga Kota Magelang - Sarno Widodo; Nitis Aruming Firdaus (Universitas Prof. Dr. Hazairin, S.H, 2018)
Population growth and changes of community consumption patterns lead to the increasingly diverse volumes, types and characteristics of waste. Meanwhile, the waste management used so far has not been appropriate to the methods and techniques of waste management based environment, which leads to a negative impact on public health and the environment. The study of the occurrence and composition of waste in the city of Magelang is intended to determine the volume/weight and composition of the waste that is the percentage of a type of waste occurrence. In this study, the method used was direct measurement method of waste occurrence units from 59 samples of family heads (KK) consisting of 6 families of lower-economic groups (Li), 27 families of middle-economic groups (MI), and 26 families of upper-economic groups (Hi). The collection of waste samples was determined proportionally and randomly at the source for 8 consecutive days. The results of the study of the occurrence and composition of municipal waste in Magelang showed that per capita waste occurrence per day in the city of Magelang was 2.58 liters/person/day, equivalent to 0.304 kg/person/day. The daily occurrence waste of the residences in the City of Magelang is 339,678 liters/day or 40,024 kg/day. While the composition of residential waste in the city of Magelang in 2016 was 54.97% organic and 45.03% inorganic. The organic waste consists of 12.65% leaf waste, 40.18% leftovers, and 2.14% twigs/wood. Meanwhile, the inorganic waste consists of 10.37% paper, 16.31% plastic, 2.23% metal, 2.86% glass/ceramic, 2.27% rubber/leather, 2.54% fabric, and 8.47% others (pampers, pads, etc.).